(untitled) (Contemporary Journal of Social Science Review, 2026)
As a result of growing political polarization, fragile democracies, spread of digital disinformation, intolerance, and increased globalization; the demand for responsible citizens has become more critical than ever. Contemporary societies require young people who are not only academically competent but also socially responsible, ethically grounded, culturally responsive, and civically engaged. Through a critical analysis of the current state of citizenship education, this article evaluates the necessity of teaching citizenship at K-12 level. This analysis is based on a comprehensive review of the most recent literature on citizenship education and various educational frameworks used internationally. In addition to examining the ways in which citizenship education promotes democracy, peaceful resolution of conflicts, critical thinking, social cohesiveness, intercultural understanding, human rights awareness, and sustainable development; the article examines how schools can cultivate civic identity in young people. Using a qualitative literature review methodology, the study examined and synthesized evidence from recent academic research on citizenship education, UNESCO educational frameworks, and government policy documents. The findings indicate that effective citizenship education strengthens civic competencies, moral reasoning, participatory skills, and respect for diversity among learners. The review also highlights the importance of experiential learning, democratic school culture, and inclusive pedagogical practices in fostering active citizenship. The article concludes by emphasizing the urgent need to integrate citizenship education into K–12 curricula, teacher education programs, and educational policies, particularly in developing countries facing democratic, social, and educational challenges.